Comparison of surgical outcomes in elective sigmoid resection for diverticulitis in different indication-specific strategies: A propensity-score matched cohort study with 636 patients. (1st June 2022) - Nocera, F; Haak, F; Ly, C; Posabella, A; Angehrn, F; von Flüe, M; Steinemann, D C
Abstract: Objective: Comparing different surgical guidelines for recurrent uncomplicated diverticulitis, a careful benefit-risk assessment is recommended although different approaches giving the indication for surgery exists. The purpose of this study was to evaluate the impact of indications-specific strategies on surgical outcomes allowing adequate benefit-risk consulting. Methods: All patients undergoing elective colonic resection for diverticulitis between January 2011 and March 2020 in our institution were included. They were divided into two groups based on the strategy for surgical indication: relative surgery indication group (RSI; CDD (classification of diverticula disease) Type 2a, 3a and 3b, n = 585) and absolute surgery indication group (ASI; CDD Type 2b and 3c, n = 318). Propensity score-matching (PSM) was applied at a ratio of 1:1 to compare the RSI and the ASI group. Results: In the univariate analysis, RSI patients were younger (62±10.4 vs. 67.7±11.4, p<0.05), had a higher physical status (ASA score 1 or 2 in 80.7% vs. 60.8%, p<0.05), were less immunosuppressed (3.4% vs. 6.9%, p<0.05) and suffered less from coronary heart disease (3.8% vs. 7.2%, p<0.05). After PSM, 318 vs. 318 patients were selected and baseline characteristics resulted comparable. The proportion of laparoscopic resection was 94.7% in RSI versus 84.6% in ASI (p<0.05) and the conversion rate to open surgery for laparoscopic resection was 5.0% in RSI and 13.8% in ASI (p<0.05). Intraoperative complications were rare in both groups (3.1% vs. 5.3%, p=0.24). Mean operation time was shorter in RSI (211±62 vs. 229±72, p<0.05). Major morbidity (Clavien/Dindo ≥3b) occurred less frequently in RSI (3.8% vs. 10.1%, p<0.05) and the overall comprehensive complications index (CCI) was lower in RSI (9.4±12.2 vs. 12.9±14.9, p<0.05). Anastomotic insufficiency occurred in 0.9% in RSI and in 2.5% in ASI (p=0.22). A defunctioning stoma was received by 0.9% in RSI and 11.0% in ASI (p<0.05). Conclusion: Our study demonstrates that even after PSM analysis patients with RSI in contrast to patients with more advanced diverticular disease have a lower risk of suffering from postoperative overall morbidity and major morbidities as well as the risk of receiving a temporary stoma. These observations should be considered when counselling patients with an equivocal indication for surgery for diverticular disease.